2014
DOI: 10.1161/strokeaha.114.005539
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Pelvic Magnetic Resonance Venography in Patients With Cryptogenic Stroke and Patent Foramen Ovale

Abstract: Background and Purpose— Paradoxical embolization is frequently posited as a mechanism of ischemic stroke in patients with patent foramen ovale. Several studies have suggested that the deep lower extremity and pelvic veins might be an embolic source in cryptogenic stroke (CS) patients with patent foramen ovale. Methods— Consecutive adult patients with ischemic stroke or transient ischemic attack and a patent foramen ovale who underwent pelvic magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 30 publications
2
30
0
4
Order By: Relevance
“…56,57 In 1 study, when compared with patients with known etiology for stroke, the rates of pelvic DVT in cryptogenic stroke were higher (20% vs. 4%), 58 though another more recent study showed no differences in the rates of DVT. 59 In addition, studies have shown that the prevalence of the otherwise rare May-Thurner syndrome (an anatomic vascular variant that predisposes towards development of DVT) in patients with cryptogenic stroke and PFO is approximately 6-8%. 60,61 Despite these conflicting results, pelvic vein thrombosis may still be an important source of thrombi in patients with cryptogenic stroke and DVT.…”
Section: Medical Therapymentioning
confidence: 99%
“…56,57 In 1 study, when compared with patients with known etiology for stroke, the rates of pelvic DVT in cryptogenic stroke were higher (20% vs. 4%), 58 though another more recent study showed no differences in the rates of DVT. 59 In addition, studies have shown that the prevalence of the otherwise rare May-Thurner syndrome (an anatomic vascular variant that predisposes towards development of DVT) in patients with cryptogenic stroke and PFO is approximately 6-8%. 60,61 Despite these conflicting results, pelvic vein thrombosis may still be an important source of thrombi in patients with cryptogenic stroke and DVT.…”
Section: Medical Therapymentioning
confidence: 99%
“…There are no published guidelines for the assessment of pelvic veins as part of the stroke workup and few studies have systematically investigated pelvic veins as a potential source for paradoxical emboli in CS patients [6,10,12]. Moreover, data from the two larger studies have been conflicting with almost tenfold different prevalence rates (ranging from 2% [12] to 20% [6]).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data from the two larger studies have been conflicting with almost tenfold different prevalence rates (ranging from 2% [12] to 20% [6]). However, differences in the extent of diagnostic workup, classification of cryptogenic stroke, differences in imaging modalities and interpretation as well as different inclusion and exclusion criteria may partially account for this variability [6,12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Indeed, a venous source of embolism is only rarely documented in patients with CS and a PFO; in the recent RE-SPECT (randomized evaluation of recurrent stroke comparing pfo closure to established current standard of care treatment) trial the prevalence of deep vein thrombosis (DVT) was 3.6% in the whole study population. 19 Notably, recent reports suggest that a MRI venogram performed early after a CS can diagnose a peripheral or pelvic venous thrombosis in up to 8% of the patients with a PFO 20,21 also showing congenital anomalies of the pelvic veins possibly predisposing to DVT in an additional 10% of them. 22 Combined computed tomography (CT) venography and pulmonary angiography recently yielded similar results with respect to prevalence of DVT, diagnosing a silent pulmonary embolism in 4.4% of the patients as well.…”
Section: Patent Foramen Ovale and Cryptogenic Cerebrovascular Or Systmentioning
confidence: 99%